The Effects of Quartz Sand Variation as an Additive on Concrete Compressive Strength (No Air Added) - Faisal, Faisal; Sutandar, Erwin; Supriyadi, Asep (Jurnal Teknik Sipil, 2025)
Concrete is a composite material widely used in construction due to its high compressive strength. However, variations in constituent materials can influence its quality and durability. One approach to improving concrete performance is to add quartz sand (SiO₂) as an additive. This study aims to analyse the effect of varying quartz sand content (0%, 5%, and 10%) on the compressive strength of non-air-entrained concrete. The research employed an experimental laboratory approach, producing cylindrical specimens cured for 28 days and tested using a compression testing machine in accordance with SNI 1974:2011. The test results showed that concrete with a 5% quartz sand addition achieved the highest compressive strength of 26.483 MPa, followed by regular concrete (26.087 MPa) and concrete with a 10% quartz sand addition (23.824 MPa). The results indicate that a moderate addition of quartz sand effectively enhances the compressive strength and density of concrete, whereas excessive dosage tends to increase porosity and reduce strength. Overall, 5% quartz sand is recommended as the optimal proportion to improve the performance of conventional concrete.